Challenges in feeding livestock: from wastes to feed - Alimon, Abdul Razak (Bahagian Komunikasi Korporat, Universiti Putra Malaysia, 2005)
The livestock industry is highly dependent on available and cheap feedstuff. Competition between man and animal for the same food is increasing. Subsequently, the search for alternatives to feed livestock must go on. Waste materials from agro-industry are possible alternatives to the traditional feedstuffs which are continuously increasing in price and scarsity. This paper discusses some of the methods and possible ways of using wastes products from the agricultural sector. Materials like rice straw has been used as animal feed but its use is declining. Many rice farmers no longer keep buffaloes or cattle and therefore the need to use the straw is diminishing. Palm byproducts, such as palm kernel cake, are useful and contribute towards the country's foreign exchange. About 1.7 million tonnes of palm kernel cake is exported annually bringing an income of about RM400 million. However, the livestock industry is deprived of the palm kernel cake which if used locally can support more than half a million heads of cattle. Other byproducts such as rice straw, palm fronds, rice bran and corn stover are not produced in such large quantities, but if the process of collecting and processing to improve their quality can be consolidated as a viable industry much of the feed imports can be reduced. Newer technologies need to be developed with considerations of reducing labour and related costs in the methods of collecting, processing, storage and distribution.